(untitled) (Journal of Renal and Hepatic Disorders, 2023)
To study the incidence of pulmonary hypertension (PH) in chronic kidney disease (CKD) stage V patients on maintenance hemodialysis (HD) at our center. To compare clinical and metabolic variables among CKD patients with and without PH to search for possible etiologic factors. Comparison of PH in CKD patients at baseline and after 3 months of sildenafil therapy. The study was conducted in the Department of Nephrology, Sri Aurob-indo Institute of Medical Sciences, Indore, for a period of 1 year from December 2021 to November 2022. All CKD patients on maintenance HD at our center were included in the study. A pre-structured proforma was used to record patient data. Detailed clinical examination, 2DECHO, and Biochemical tests were done. All patients with mean pulmonary artery pressure (mPAP) > 25 mmHg on 2D echocardiography were considered to have PH and were started on sildenafil therapy 20 mg three times a day for 3 months. PH was classified as mild PH (mPAP > 25 up to 40 mmHg), moderate PH (mPAP > 40 mmHg to 60 mmHg), and severe PH (mPAP > 60 mmHg). Patients were then followed for 3 months to look for episodes of dyspnea and emergency admissions and reassessed after 3 months by repeat 2D echocardiography to find improvement in PH. A total of 102 patients were analyzed during the study period; among them, 40 patients (39.2%) had PH. Out of them, 18 patients (45%) had mild PH, 14 patients (35%) had moderate PH, and 8 patients (20%) patients had severe PH. Average age of our patients was 48.8 ± 9.4 years, the majority being men. On comparing the clinical features between patients with and without PH, none of the clinical parameters had any statistically significant impact on PH. Also, none of the laboratory parameters had statistical significance among PH and non-PH groups. Among the patients with PH, 25 patients (62.5%) had Arteriovenous (AV) fistula, 10 patients (25%) had temporary dialysis catheters. Eight patients (20%) had jugular catheters, two patients (5%) had femoral catheters, and 5 (12.5%) patients had tunneled jugular catheters. Initially, 102 patients were enrolled in the study. Of these, 40 (39.2%) had PH and 62 (60.7%) did not. Patients who had PH started sildenafil 20 mg three times a day. Of these 40 patients, at 3 months, eight patients were lost to follow-up, and 32 patients with PH remained in the study. Emergency admissions in each group of PH declined after 3 months, and the result was statistically significant. Echocardiographic findings were compared in patients with PH and without PH, but the difference in patients on HD with PH and without PH was not statistically significant. PH is a significant problem in CKD patients on HD. This issue needs to be evaluated in a timely manner to avoid the risk of morbidity and mortality. It is vital to treat them at the earliest to prevent life-threatening complications.